All-optical processing based on integrated optics - Almeida, Luis Miguel Lima de (2015)
During the last years, the demand for high data transfer rates in optical fiber communications has increased exponentially. Since image in its original format exactly as it is captured by the digital camera requires an enormous amount of storage capacity, it is important to develop a system that increases its amount of compression while preserving the important image’s information. In the topic of image’s compression, there are several transformation techniques used for data compression. Discrete Wavelet Transform (DWT) is one of the most commonly used, thanks to its multi-resolution transformation. This multi-resolution property allows to develop, not only a lossless compression method, from which the original image can be obtained exactly as it was before the transform, but also, a lossy method where it is not possible to obtain the original image. In this context, this thesis will develop the idea to apply the Haar wavelet transform using optical circuits. This concept will be analyzed, verifying the possibility of its implementation in the optical domain, using several methods, lossy and lossless, to conclude about the best compression method to apply to an image. Finally, the lossy method will be tested in the laboratory with different components and design the optical device able to accomplish the Haar wavelet transform.